Co‐culture of bone marrow‐derived mesenchymal stem cells overexpressing lipocalin 2 with HK‐2 and HEK293 cells protects the kidney cells against cisplatin‐induced injury. (1st August 2014) - Halabian, Raheleh; Roudkenar, Mehryar Habibi; Jahanian‐Najafabadi, Ali; Hosseini, Kamran Mousavi; Tehrani, Hossein Abdul
Abstract Conditioned medium of mesenchymal stem cells (MSCs) is now being used for its cytoprotective effects, especially when the cells are equipped with cytoprotective factors to strengthen them against unfavorable microenvironments. Overexpression of Lcn2 in MSCs mimics in vivo kidney injury. Hence, unraveling how Lcn2‐engineered MSCs affect kidney cells has been investigated. Cisplatin treated HK‐2 or HEK293 kidney cells were co‐cultivated with Lcn2 overexpressing MSCs in upper and lower chambers of transwell plates. Proliferation, apoptosis, and expression of growth factors and cytokines were assessed in the kidney cells. Co‐cultivation with the MSCs‐Lcn2 not only inhibited cisplatin‐induced cytotoxicity in the HK‐2 and HEK293 cells, but increased proliferation rate, prevented cisplatin‐induced apoptosis, and increased expression of growth factors and the amount of antioxidants in the kidney cells. Thus Lcn2‐engineered MSCs can ameliorate and repair injured kidney cells in vitro, which strongly suggests there are beneficial effects of the MSCs‐Lcn2 in cell therapy of kidney injury.